2019
DOI: 10.3389/fonc.2019.01102
|View full text |Cite
|
Sign up to set email alerts
|

GOLFIG Chemo-Immunotherapy in Metastatic Colorectal Cancer Patients. A Critical Review on a Long-Lasting Follow-Up

Abstract: Background: GOLFIG is a chemo-immunotherapy regimen established in preclinical models that combines gemcitabine + FOLFOX (fluoropyrimidine backbone coupled to oxaliplatin) poly-chemotherapy with low-dose s. c. recombinant interleukin-2 (rIL-2) and granulocyte-macrophage colony stimulating factor (GM-CSF). Promising antitumor effects in metastatic colorectal cancer (mCRC) patients were obtained in previous phase II and III trials. Here we report the results of 15 years of follow-up.Methods: This is a multi-inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 45 publications
(67 reference statements)
0
19
0
Order By: Relevance
“…A retrospective clinical study demonstrated that colorectal cancer patients strongly benefited from a combined chemo-immunotherapy regimen (GOLFIG) with respect to progression-free survival and overall survival. In particular, chemotherapeutically pre-treated patients displayed increased anti-tumor responses [ 31 ]. Several recent trials suggest that the antigen load is critical for an efficient treatment response and that immune-modulating treatments, including chemotherapy and RT, could increase the chance to benefit from checkpoint inhibitors and immunotherapy [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective clinical study demonstrated that colorectal cancer patients strongly benefited from a combined chemo-immunotherapy regimen (GOLFIG) with respect to progression-free survival and overall survival. In particular, chemotherapeutically pre-treated patients displayed increased anti-tumor responses [ 31 ]. Several recent trials suggest that the antigen load is critical for an efficient treatment response and that immune-modulating treatments, including chemotherapy and RT, could increase the chance to benefit from checkpoint inhibitors and immunotherapy [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gemcitabine is a nucleoside analog (2′,2′-difluorodeoxycytidine) used to treat patients with pancreatic, lung, breast, or bladder cancers. It has been occasionally combined with FOLFOX against colon cancer ( 234 ). Bacteria can metabolize the chemotherapeutic drug gemcitabine (2′,2′-difluorodeoxycytidine) into its inactive form, 2′,2′-difluorodeoxyuridine ( 211 ).…”
Section: Colon Cancer Therapies and Gut Microbiotamentioning
confidence: 99%
“…Camptothecin, a potent antineoplastic compound, poisons the catalytic cycle of human topoisomerase I. Camptothecin exhibited marked toxicity and poor bioavailability. Although its derivatives topotecan and CPT-11 (also called irinotecan) are now in clinical use ( 234 ), they still elicit pronounced side effects that limit efficacy. CPT-11 is one of the three commonly used chemotherapeutic agents for CRC ( 236 ).…”
Section: Colon Cancer Therapies and Gut Microbiotamentioning
confidence: 99%
“…CRC is the most common malignant tumor of digestive tract in the world, which seriously endangers people's health and quality of life. However, its pathogenesis has not been completely elucidated, and progression of CRC is a process that involves multiple genetic changes, multi-factor, multi-step process [17,18]. Previous studies indicate that one third of CRC patients may develop liver metastases, and most of CRC-related death is usually attributed to distant metastasis.…”
Section: Discussionmentioning
confidence: 99%